Cryptococcus humicola complex isolated before and after treatment of mastitis in cows - Baroni, Francisco de Assis; de Abreu, Daniel Paiva Barros; Lima, Diego Medeiros; de Campos, Sergio Gaspar; Paula, Claudete Rodrigues; Botteon, Rita de Cássia Campbell Machado (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Baroni F.A., Abreu D.P.B., Lima D.M., Campos S.G., Paula C.R. & Botteon R.C.C.M. [Cryptococcus humicola complex isolated before and after treatment of mastitis in cows.] Complexo Cryptococcus humicola isolado no pré e no pós-tratamento de mastite em vacas. Revista Brasileira de Medicina Veterinária, 38(Supl.2):17-21, 2016. Departamento de Microbiologia e Imunologia Veterinária, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, BR 465, Km 7, Zona Rural, Seropédica, RJ 23890-000, Brasil. E-mail: baroni@ufrrj.br The inflammatory reaction of mammary glands or mastitis is one of the main problems of dairy farming in Brazil, with huge financial losses caused to producers. It has several causes, occurring predominantly by microbial action. Although bacterial etiology is the prevalent cause of clinical and subclinical cases, fungi, algae, and viruses also have involvement. Among the fungi, Candida spp., Trichosporon spp., Cryptococcus are the most prevalent. The first involved reports of Cryptococcus yeast in cases of mastitis are old, but Cryptococcus species has been reported as emerging yeast in several clinical cases, especially in humans. In this paper, we describe the isolation of Cryptococcus humicola from milk samples collected from two animals in two different dairy farms before and after the treatment performed for bacterial mastitis and we discuss possible ways and causes of infection.